APPLICATION OF SOCIAL CONTROL THEORY ON BAGCILAR HIGH SCHOOL STUDENTS: HIRSCHI'S MODEL - AKCIGER, UMIT (2013)
The delinquency and drug problems have wide range of damaging consequences not only for the individuals involved in delinquency and illegal drug use, but also for their families and the overall community. In order to overcome such problems, understanding the causation or restraining factors in determining both delinquency and illegal substance use oriented behaviors is essential. Unfortunately, there are limited studies to understand the reasons and restraining factors of delinquency and illegal substance use within criminological theories in Turkey. However, there are outnumber studies carried out to test the validity of various criminological theories in explaining delinquency and illegal substance use in other Western country cases. Among such theories, ‘social control theory’, as one of the most accepted and strongest criminological theories, has been tested in those countries. However, limited numbers of studies have been conducted on ‘social control theory’ in the countries where traditional values are still dominant, such as Turkey. Therefore, this study aims to fill this gap in the case of Turkey. The aim of this study, hence, is to measure the nexus between social control elements and both delinquency and illegal substance use among Bagcilar High School students within the theoretical framework of ‘social control theory’. Bagcilar is the biggest borough of Istanbul, which has received migration from different parts of Turkey in the last thirty years with different cultural backgrounds. Therefore, it is one of the cosmopolitan parts of the Istanbul city with its population diversity. In fulfilling the aim of the study, secondary data has been used in testing the social control theory for which the variables have been derived from various studies based on literature review. Extensive statistical analyses were applied to the data set to measure the relationships between social control variables and delinquency and illegal substance use related behaviour, which included correlation and regression analyses. The findings show that some of the social control variables verified the social control theory in Bagcilar’s case, while others did not. As a result, social control theory with its identified variables explains 31.9 percent of delinquency and 34.5 percent of illegal substance use in overall. It is important to note that some of the variables considered to be im portant in the Turkish case such as religion could not be found as a significant variable. On the other hand, it has been observed that family structure is statistically significant on younger ages while it is not statistically significant for elders. Based on finding, policy recommendations have been made for both law enforcement agencies and other governmental institutions, because it has been widely accepted that fighting with delinquency and illegal substance use cannot be limited to law enforcement agencies, as the involvement of other social policy oriented organizations are indispensable